Remote Plasmas CVD and Reactive Sputtering in Magnetron Plasmas - Ricard , A.; Belmonte , T.; Czerwiec , T.; Konstantinidis , S. (Plasmas Afterglows with \(N_2\) for Surface Treatments- Edition 2, 2022)
Two optical optical spectroscopy methods have been applied to the determination of B-atoms and Ce-atoms absolute densities. The first one on B-atoms was applied to a remote microwave plasma. At the plasma end, the B-atom density nearly reach , which corresponds to a dissociation degree of about . It was observed the reactions of -atoms on desorbing from the tube wall after -atoms collisions. The second optical spectroscopy is the resonant absorption applied to - atoms produced in a DC magnetron sputtering of a Ce cathode. In pure Ar plasmas, the Ce density was . By introducing in the Ar plasma, it was observed an hysteresis effect of Ce density as for the plasma voltage.